EFFECTIVENESS OF LEARNING FORMATS UNDER UNSTABLE CONDITIONS: EDUCATIONAL PROCESS IN PRIMARY SCHOOL - Topuzov, Oleh; Onopriienko, Oksana; Petruk, Oksana; Lipchevska, Inna; Pavlova, Tetiana (Information technologies and learning tools, 2025)
The article presents a comparative analysis of the effectiveness of different learning formats in primary school under prolonged instability caused by the COVID-19 pandemic and martial law in Ukraine. The study examines face-to-face, distance, blended and hybrid learning. The research is based on the results of a nationwide survey of teachers and parents of students in grades 1–4, conducted by researchers from the Institute of Pedagogy of the National Academy of Educational Sciences of Ukraine in 2024. The analysis of respondents’ answers enabled the comparison of teachers’ and parents’ perspectives on different learning formats. The obtained results are presented in the context of comparing effectiveness between urban and rural schools. The impact of the learning format on the academic performance of students in grades 1–2 and 3–4 was determined. It was established that face-to-face learning remains optimal for primary school students, particularly for grades 1–2 during the adaptation stage to the school environment. Distance learning can be effective if there is adequate methodological support, a sufficient level of digital competence, and high-quality technological infrastructure. Students in grades 3–4 show better adaptation to distance learning compared to younger students. Blended and hybrid learning, despite their flexibility, may complicate students’ concentration and ability to stay organized due to frequent changes in interaction formats. Regardless of the format, the greatest learning losses were recorded in language-literary and mathematical education. At the same time, parents emphasize not only the complexity of primary education content but also the excessively high pace of its acquisition, which complicates material comprehension. Therefore, it is advisable to direct the educational process in grades 1–4 toward the formation of students’ functional literacy. Such an approach will help reduce educational losses and create a strong foundation for students’ successful learning in basic school. The obtained results have practical significance for developing strategies to optimize the educational process in conditions of prolonged instability both in Ukraine and in other countries facing similar challenges in organizing education. У статті здійснено порівняльний аналіз ефективності різних форматів навчання в початковій школі за умов тривалої нестабільності, спричиненої пандемією COVID-19 і воєнним станом в Україні. Розглянуто очне, дистанційне, змішане / гібридне навчання. Дослідження ґрунтується на результатах всеукраїнського опитування вчителів і батьків учнів 1–4 класів, проведеного науковцями Інституту педагогіки НАПН України у 2024 році. Аналіз відповідей респондентів дав змогу порівняти погляди вчителів і батьків на різні формати навчання. Отримані результати подано в контексті зіставлення ефективності міських і сільських шкіл. Визначено вплив формату навчання на навчальні результати учнів 1‒2 і 3‒4 класів. Встановлено, що очне навчання залишається оптимальним для учнів початкової школи, особливо для 1–2 класів на етапі адаптації до шкільного середовища. Дистанційний формат може бути ефективним за наявності належної методичної підтримки, достатнього рівня цифрових компетентностей та якісної технологічної інфраструктури. Учні 3–4 класів демонструють кращу адаптацію до дистанційного навчання порівняно з молодшими школярами. Змішане та гібридне навчання, попри свою гнучкість, можуть ускладнювати концентрацію уваги й організованість учнів через часті зміни форм взаємодії. Незалежно від формату, найбільші навчальні втрати зафіксовано в мовно-літературній і математичній освітніх галузях. Водночас батьки наголошують не лише на складності змісту початкової освіти, але й на надмірно високому темпі його засвоєння, що ускладнює сприйняття матеріалу. Тому доцільно спрямувати освітній процес у 1–4 класах на формування функційної грамотності учнів. Такий підхід допоможе зменшити освітні втрати та створити міцну основу для успішного навчання учнів у базовій школі. Отримані результати мають практичне значення для розробки стратегій оптимізації освітнього процесу в умовах тривалої нестабільності як в Україні, так і в інших країнах, які мають аналогічні виклики щодо організації навчання.